1997
DOI: 10.1039/a607616e
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatographic Determination Using Lanthanides as Time-Resolved Luminescence Probes for Drugs and Xenobiotics: Advantages and Limitations

Abstract: Lanthanide sensitized luminescence is a very attractive alternative to UV detection and other luminescence techniques, i.e., fluorescence and phosphorescence, in separation science for the detection of drugs and xenobiotics because of the large Stokes shift, narrow emission bands and long lifetime. Some published applications of HPLC determination with lanthanide (Ln3+) sensitized luminescence detection are reviewed. Advantages and limitations of this technique are discussed. Normal-phase (NP) HPLC is not infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 36 publications
0
29
0
2
Order By: Relevance
“…These results suggest that non-ionic surfactants are more effective in protecting against non-radiative processes. In a previous study, it was suggested that micelles provide a discrete volume region for inclusion of the lanthanide ion and the ligand, so that the energy transfer process is facilitated (37). In particular, micelles create non-polar regions in the aqueous solution and allow the removal of the quenching effect of water in the aqueous system (38,39).…”
Section: Effect Of Buffermentioning
confidence: 98%
“…These results suggest that non-ionic surfactants are more effective in protecting against non-radiative processes. In a previous study, it was suggested that micelles provide a discrete volume region for inclusion of the lanthanide ion and the ligand, so that the energy transfer process is facilitated (37). In particular, micelles create non-polar regions in the aqueous solution and allow the removal of the quenching effect of water in the aqueous system (38,39).…”
Section: Effect Of Buffermentioning
confidence: 98%
“…For instance, the levels of some lanthanide complexes with fqH in various environmental samples (water, food, urine, etc.) have been investigated [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Tris buffer is known to have chelating properties with lanthanide ions [20,21]. Hence, it is necessary to optimize the concentration that will afford maximum sensitization of the Eu-PX system.…”
Section: Effect Of Concentration Of Tris Buffermentioning
confidence: 99%